2021
DOI: 10.3390/agriculture12010001
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Arbuscular Mycorrhizal Colonization in Walnut Plantations: The Contribution of Cover Crops and Soil Microbial Communities

Abstract: Soil microorganisms play a central role in biological soil functioning. One of the beneficial microbiota that has a symbiotic association with most of the plants is arbuscular mycorrhizal fungi (AMF). Nevertheless, little is known about the impact of cover crops—widely used in conservation agriculture or organic farming—on native mycorrhizal fungi. This study was conducted in Southern France, in 20-year-old walnut orchards, where faba bean (Vicia faba Roth) was intercropped. To find whether the native AM funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Behrooz et al (2019) reported that AMF (G. mosseae and G. etunicatum) significantly increased contents of some metabolites (e.g., total phenols and proline) in walnut plants under DS. Moreover, AMF also promoted plant growth and nutrient acquisition in walnut plants (Thioye et al, 2022), and thereby improved the adaption of walnut plants in response to DS. The study of Liu et al (2021) showed the an endophytic fungus (Serendipita indica) triggered the enhancement in superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) activities in walnut plants under soil water deficit, accompanied by the reduction of superoxide anion free radical (O 2…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Behrooz et al (2019) reported that AMF (G. mosseae and G. etunicatum) significantly increased contents of some metabolites (e.g., total phenols and proline) in walnut plants under DS. Moreover, AMF also promoted plant growth and nutrient acquisition in walnut plants (Thioye et al, 2022), and thereby improved the adaption of walnut plants in response to DS. The study of Liu et al (2021) showed the an endophytic fungus (Serendipita indica) triggered the enhancement in superoxide dismutase (SOD), catalase (CAT), and peroxidase (POD) activities in walnut plants under soil water deficit, accompanied by the reduction of superoxide anion free radical (O 2…”
Section: Introductionmentioning
confidence: 95%
“…Combining AMF ( Glomus fasciculatus ) inoculation with foliar fertilization would increase plant growth as well as the survival of walnuts ( Ponder, 1984 ). In addition, AMF ( Diversispora spurca ) inoculation accelerated nutrient uptake of walnuts such as P and K ( Huang et al., 2020 ; Thioye et al., 2022 ). Potted studies had shown the role of AMF in drought tolerance of walnut plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…occurring between soil functions and soil-based ecosystem services [41]. Therefore, the evaluation of biological indicators of soil quality is necessary to link the microbial community composition and activity to the changes in the soil abiotic properties [39]. Multi-substrate induced respiration (multi-SIR) is a sensitive method used to determine the catabolic fingerprint of microbial communities [42].…”
Section: Fym + Achilleamentioning
confidence: 99%
“…Microbial biomass indices reflect the availability of C, N, S, and P in soil [36,37]. Consequently, they are key components for assessing soil fertility and quality [38,39] in different agricultural management systems [13,28,38,40]. Soil quality is defined as the capacity of a soil to function within ecosystem to maintain key biological functions, environmental quality, and promote plant and animal health [38,41].…”
Section: Introductionmentioning
confidence: 99%